Comparision of Myocardial Viability Assessment Between Cardiac Magnetic Resonance Imaging and Single Photon Emission Computed Tomography in Patients with Coronary Artery Disease - Ahmed, Iftikhar; Nadeem, Asif; Saif, Mohsin; Saeed, Nazish; Ali, Jahanzab; Anwar, Maida; Fayyaz, Muhammad; Mustafa, Attiya (Pakistan Armed Forces Medical Journal, 2022)
Objective: To assess the myocardial viability on cardiac magnetic resonance imaging compared with single photon emission computed tomography scan in patients with coronary artery disease. Study Design: This study was cross sectional study. Place and Duration of Study: Cardiac Magnetic Resonance Imaging and Nuclear Medicine Departments of a Tertiary Cardiac Care Center of Rawalpindi Pakistan, from Dec 2021 to May 2022. Methodology: This study was cross sectional study conducted from December 2021 to May 2022 at Cardiac Magnetic resonance imaging and Nuclear Medicine departments of a Tertiary Cardiac Care Center of Rawalpindi Pakistan. Thirty patients (n=30) with coronary artery disease were selected using non-probability consecutive sampling technique to determine the viable myocardium using cardiac magnetic resonance imaging (CMR) and single photon emission computed tomography (SPECT) scan. Patients with left ventricular dysfunction having ejection fraction equal to or less than forty-five percent and coronary artery disease were included. Results: Using 20 segment models, the mean number of viable segments in SPECT scan and CMR were 16.6±3.18 and 15.47±3.84, respectively while the non-viable segments were 3.4±3.1 and 5.17±4.6, respectively. There was statically little difference in results of Single-photon Emission Computerized Tomography and Cardiac Magnetic Resonance Imaging to determine viable myocardium (p<0.05). Conclusion: Assessment of myocardial viability has keen role in diagnostic and prognostic work up of coronary artery disease patients who are candidates of revascularization. Stunned and hibernating myocardium are two states oreversible myocardial dysfunction.....